Global biogeography and projection of antimicrobial toxin genes - Ya Liu; Yu Geng; Yiru Jiang; Jingyu Sun; Peng Li; Yue-zhong Li; Zheng Zhang (Microbiome)
Abstract Background Antimicrobial toxin genes (ATGs) encode potent antimicrobial weapons in nature that rival antibiotics, significantly impacting microbial survival and offering potential benefits for human health. However, the drivers of their global diversity and biogeography remain unknown. Results Here, we identified 4400 ATG clusters from 149 families by correlating 10,000 samples worldwide with over 200,000 microbial genome data. We demonstrated that global microbial communities universally encode complex and diverse ATGs, with widespread differences across various habitats. Most ATG clusters were rare within habitats but were shared among habitats. Compared with those in animal-associated habitats, ATG clusters in human-associated habitats exhibit greater diversity and a greater proportion of sharing with natural habitats. We generated a global atlas of ATG distribution, identifying anthropogenic factors as crucial in explaining ATG diversity hotspots. Conclusions Our study provides baseline information on the global distribution of antimicrobial toxins by combining community samples, genome sequences, and environmental constraints. Our results highlight the natural environment as a reservoir of antimicrobial toxins, advance the understanding of the global distribution of these antimicrobial weapons, and aid their application in clinical, agricultural, and industrial fields. Video Abstract